Faktor-Faktor Risiko Hipertensi Sistolik Terisolasi pada Lanjut Usia - Abdul Farid Lewa, I Dewa Putu Pramantara, Th. Baning Rahayujati (Fakultas Kedokteran Universitas Gadjah Mada, 2010)
Background: Elderly period is the final period of development in human life cycle. One reaches elderly period when he or she is >60 years old. US Census Bureau in WHO Report projects that in 2000-2030 world population of >60 years old will increase from 6.9% to 12.0% with the biggest increase in developing countries. Isolated systolic hypertension (ISH) is an important cardiovascular risk factor in the elderly as indicated from systolic blood pressure >140mmHg and diastolic pressure <90mmHg. One of causes of increasing blood pressure in the elderly population is ISH. Its prevalence and incidence increase in line with increasing age and it is estimated that 55% of population will have hypertension at the age of 60 years and 65% at the age of > 70 years. In elderly population with hypertension 65% of them have ISH.Objective: The study aimed to identify risk factors of ISH among the elderly at Kalibawang, District of Kulon Progo, Province of Yogyakarta Special Territory.Method: The study was observational with case control study design. Subject of the study were elderly of >60 years old based on inclusion and exclusion criteria. Subject consisted of 238 people comprising 119 cases and 119 controls. Analysis used chi square test (X2) at significance 95% and multiple logistic regression to identify dominant factors in the prevalence of ISH.Result: Variables of smoking habit, psychosocial stress and physical activity were risk factors for the prevalence of ISH in the elderly at Kalibawang where by smoking habit OR =3.353 (95% CI 1.375-8.172); psychosocial stress OR = 2.449 (95% CI 1,408-4,260) and less physical activity, OR =1.970 (95% CI 1.110-3.495).Conclusion: Smoking habit (OR=3.35), psychosocial stress (OR=2.44) and less physical activity (OR=1.97) where as obesity was not risk factor for the prevalence of ISH.Keywords: Risk factors, isolated systolic hypertension, elderly